1999
DOI: 10.1523/jneurosci.19-05-01657.1999
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Tolerance in Murine Cortical Cell Culture: Critical Role for NMDA Receptors

Abstract: Murine cortical cultures containing both neurons and glia (days in vitro 13-15) were exposed to periods of oxygen-glucose deprivation (5-30 min) too brief to induce neuronal death. Cultures "preconditioned" by sublethal oxygen-glucose deprivation exhibited 30-50% less neuronal death than controls when exposed to a 45-55 min period of oxygen-glucose deprivation 24 hr later. This preconditioning-induced neuroprotection was specific in that neuronal death induced by exposure to excitotoxins or to staurosporine wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
159
0
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(174 citation statements)
references
References 51 publications
(61 reference statements)
13
159
0
2
Order By: Relevance
“…Bond et al reported that the non-competitive NMDA receptor antagonist MK-801 and the competitive NMDA receptor antagonist LY202157 all produced significant reductions in the induced ischemic tolerance, suggesting that mild NMDA receptor activation is involved in the neuroprotective mechanism of BIP [9] . Consistent with these findings, exposure of cortical cell cultures to low levels of glutamate or NMDA to induce NMDA receptor activation has a preconditioning effect [10] .…”
Section: Excitatory/inhibitory Neurotransmitters and Neuroprotectionsupporting
confidence: 53%
“…Bond et al reported that the non-competitive NMDA receptor antagonist MK-801 and the competitive NMDA receptor antagonist LY202157 all produced significant reductions in the induced ischemic tolerance, suggesting that mild NMDA receptor activation is involved in the neuroprotective mechanism of BIP [9] . Consistent with these findings, exposure of cortical cell cultures to low levels of glutamate or NMDA to induce NMDA receptor activation has a preconditioning effect [10] .…”
Section: Excitatory/inhibitory Neurotransmitters and Neuroprotectionsupporting
confidence: 53%
“…1C and F). Previous studies (Grabb and Choi, 1999;Kato et al, 1992) have suggested that the activation of NMDA receptors of neurons is essential to the PC-induced ischemic tolerance of neurons. Thus, we then investigated whether the activation of NMDA receptors was also involved in the neuronal ischemic tolerance 13 in our culture system.…”
Section: Resultsmentioning
confidence: 99%
“…45 It has been suggested that mild activation of NMDA receptors is a central mechanism of developing ischemic tolerance. [46][47][48] Although several other interesting studies have demonstrated potential neuroprotective properties of different factors investigated in the context of HD, none of these factors have afforded the same dramatic protection against excitotoxicity as is in the transgenic HD mouse models we have described in this review article (see e.g. Saydoff et al, 49 Dedeoglu et al, 50 McBride et al, 51 Jin et al 52 and Ferrante et al 53 ).…”
Section: Possible Mechanisms Involved In Huntingtin-mediated Resistancementioning
confidence: 86%